Report by Dawson on his work in Newcastle to publish the British Worker, 27 May 1926 (page 2)
1926-05-27 "Report by Dawson on his work in Newcastle to publish the British Worker, 27 May 1926 (page 2)" [g0736002.jpg], 27 May 1926, Dawson